The Concept Of Qaṭ’ī Dalālah: Definition, Laws, And Perceived Conflict - Maulidizen, Ahmad; Pratiwi, Eka (Khatulistiwa, 2020)
In terms of methods of discovering Islamic law, experts formulated 3 methods, namely: linguistic interpretation methods, kaukasi methods and theological methods. The mention of the method of discovery of the first type of law as bayani reasoning means that the discussion is more focused on text, in this case the text is Arabic. This method is a method of legal discovery by interpreting or interpreting existing Islamic legal texts, namely the Quran and hadith. Urgency of sharia is based on the understanding of the verses (verses) of the law in the Qur'an and hadith, the process of decomposition, deepening, and formulation of the law based on a collection of sources from the Qur'an and Hadith. Clear Lafaz is a clear explanation its designation of the intended meaning without requiring an outside explanation. Lafaz, whose meaning is clear, there are 2 opinions, the first is the opinion of the jumhur ulama or mutakallimun, explaining that the meaning of Lafaz is divided into three levels, namely Nash, Zahir and Mujmal. While other opinions, namely opinions from the Hanafi. Lafaz which is clear according to hanafiyah there are 4 kinds, namely: zahir, nash, mufassar and muhkam